PERKEMBANGAN OBJEK WISATA BAHARI DI KOTA PARIAMAN - Devitriana Riana; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine the development of marine tourism objects in Pariaman City in terms of attractions, amenities, accommodation, and accessibility aspects in the period 2003-2008, 2008-2013, 2013-2018, 2018-2020. This type of research is classified as Mix Methods. The data sources in this research are primary data and secondary data. Collecting data by observation, interviews and documentation. The data analysis used is a quantitative approach.The subjects in this study were taken using accident sampling technique. The number of subjects as many as 24 people, namely the Head of the Development of Destinations and Tourism Attractions in Kota Pariaman, managers, communities and traders around tourist objects and tourists. The results of this study are: the development of marine tourism objects in Kota Pariaman based on the aspects of tourist attractions, tourism accommodation, and tourism amenities in the period 2003-2008, 2008-2013, 2013-2018 and 2018-2020 has increased in each period. However, based on the aspect of tourism accessibility in the period 2003-2008, 2008-2013, 2013-2018, and 2018-2020, based on the condition of the road surface in good, moderate, damaged and heavily damaged conditions in each period it fluctuates.